2019
DOI: 10.3390/soilsystems3020034
|View full text |Cite
|
Sign up to set email alerts
|

What is the Best Inference Trajectory for Mapping Soil Functions: An Example of Mapping Soil Available Water Capacity over Languedoc Roussillon (France)

Abstract: Extending digital soil mapping to the mapping of soil functions that can support end-user decisions comes to coupling a digital soil mapping procedure and a soil function assessment method. This can be done following various possible inference trajectories following the order with which “combining primary soil properties”, “aggregating soil layers across depths” and “mapping” are executed to provide the targeted output. Eighteen inference trajectories, designed for computing soil available water capacity maps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…We used a direct mapping approach for modelling the spatial distribution of SOC stocks in 1992 and 2010, and then derived the SOC stock change between the two years since the cokriging approach yields coherent results as we pointed out in Section 4.2. However, there are further alternative trajectories or approaches (Heuvelink and Pebesma, 1999;Styc and Lagacherie, 2019) that may be interesting to check and compare with the approach used in this study, since Styc and Lagacherie (2019) observed important differences of performances between such inference trajectories.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…We used a direct mapping approach for modelling the spatial distribution of SOC stocks in 1992 and 2010, and then derived the SOC stock change between the two years since the cokriging approach yields coherent results as we pointed out in Section 4.2. However, there are further alternative trajectories or approaches (Heuvelink and Pebesma, 1999;Styc and Lagacherie, 2019) that may be interesting to check and compare with the approach used in this study, since Styc and Lagacherie (2019) observed important differences of performances between such inference trajectories.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…The soil depth map was generated using a method based on survival analysis (Chen et al, 2019; Ishwaran et al, 2008; Styc & Lagacherie, 2019) and a random forest model (Ishwaran, 2020) determining the most probable value for soil depth with a 90% confidence interval. Comparison between the predicted and observed soil depth map produced R 2 = .67 and RMSE = 0.67 m.…”
Section: Methodsmentioning
confidence: 99%
“…DSM has been increasing applied to AWC in recent years (Hong et al 2013;Jin et al 2018;Levi et al 2015;Roman Dobarco et al 2019a;Szabo et al 2019;Zare et al 2018), and several articles include pioneer considerations of rooting depth and gravel contents (Leenaars et al 2018). Styc and Lagacherie (2019) showed that performances of AWC mapping were influenced strongly by the order in which "combining primary soil properties," "aggregating soil layers across depths," and "mapping" are executed to provide the targeted AWC.…”
Section: Digital Soil Mapping Applied To Awcmentioning
confidence: 99%